The effect of workfare policy on crime - Peter Fallesen; Lars Pico Geerdsen; Susumu Imai; Torben Tranaes (Queen's University, Department of Economics, 2010)
In this paper, we focus on a novel and potentially important aspect of the workfare policy in the Danish labor market, namely its effect on crime. We do this by exploiting two policy changes. First, we examine the effect of a series of national welfare reforms introduced during the 1990s. Those reforms strengthened the work requirement for the young welfare recipients and were introduced gradually, starting with younger welfare participants first. We exploit the differential introduction of workfare reform across different age groups as the exogenous variation. Second, we use a unique policy experiment that began in 1987 by an innovative mayor of the Danish city of Farum, where he imposed a 100 % work or training requirement for all welfare recipients immediately from the date of enrollment. By comparing the changes in crime rates among the welfare recipients in Farum before and after 1987 with that of the rest of Denmark, we identify the effect of workfare on the crime rate.
Keywords: H53; J68; K42; 330; workfare; crime; welfare; Arbeitsmarktpolitik; Aktivierende Sozialhilfe; Wohlfahrtsanalyse; Kriminalität; Dänemark